Soybean isoflavones modulate gut microbiota to benefit the health weight and metabolism - Huang, Lili; Zheng, Tao; Hui, Huaying; Xie, Guozhen (Frontiers in Cellular and Infection Microbiology, 2022)
Soybean isoflavones (SIs) are widely found in food and herbal medicines. Although the pharmacological activities of SIs have been widely reported, their effects on the intestinal microecology of normal hosts have received little attention. Five-week-old Kunming (KM) mice were administered SIs (10 mg/kg/day) for 15 days. Food intake, body weight, and digestive enzyme activity were measured. Small intestine microbiota, including lumen-associated bacteria (LAB) and mucosa-associated bacteria (MAB), were analyzed using 16S ribosomal ribonucleic acid (16S rRNA) gene sequencing. Short-chain fatty acids (SCFAs) were analyzed using gas chromatography-mass spectrometry (GC-MS). The results showed that the mice that consuming SIs showed a higher food intake but a lower body weight gain rate than that of normal mice. Sucrase, cellulase, and amylase activities reduced, while protease activity increased after SIs intervention. Moreover, SIs increased the intestinal bacterial diversity in both LAB and MAB of normal mice. The composition of LAB was more sensitive to SIs than those of MAB. Lactobacillus, Adlercreutzia, Coprococcus, Ruminococcus, Butyricicoccus, and Desulfovibrio were the differential bacteria among the LAB of mice treated with SIs. In addition, acetic acid, valeric acid, isobutyric acid, isovaleric acid, and caproic acid decreased, while butyric acid and propionic acid increased in the mice treated with SIs (P > 0.05). Taken together, SIs are beneficial for weight control, even in short-term interventions. The specific mechanism is related to regulating the gut microbiota, changing digestive enzyme activities, and further affecting carbohydrate absorption and metabolism.